Suspected adverse drug interaction between spinosad and milbemycin oxime in a cat - Elizabeth L Jenkins (Journal of Feline Medicine and Surgery Open Reports, 2019)
Case summary A 12-year-old male neutered Tonkinese cat was presented for acute ataxia, weakness, altered mentation and generalised tremors. The cat had been administered oral spinosad (140 mg; 33.5 mg/kg) 48 h prior to the onset of clinical signs, and an oral anthelmintic containing milbemycin oxime (16 mg; 3.8 mg/kg) and praziquantel (40 mg; 9.6 mg/kg) 12 h before the onset of clinical signs. On physical examination, dull-to-obtunded mentation, tetraparesis, ataxia and mild tremors of facial, limb and trunk muscles were noted. Serum biochemical changes and urinalysis were consistent with haemoconcentration. The results of a complete blood count, urine culture and serology for feline leukaemia virus, feline immunodeficiency virus and cryptococcal antigen were negative. The patient was monitored in hospital and all clinical signs resolved within 24 h. Relevance and novel information The neurological signs in this case were consistent with macrocyclic lactone neurotoxicity, which is suspected to have occurred from an adverse drug interaction between spinosad and milbemycin oxime. This report serves to highlight the potential for this adverse drug interaction between these commonly used prophylactic drugs.